The structure of the surface alloy formed as a result of high-speed melting of the film (ticu)/substrate (al) system; High Temperature Material Processes: An International Quarterly of High-Technology Plasma Processes; Vol. 17, № 4 - Ivanov Y. F.; Koval N. N. Nikolay Nikolaevich; Teresov A. D.; Petrikova E. A.; Shugurov V. V.; Vlasov V. I.; Ivanova O. V.; Ikonnikova I. A.; Klopotov A. A. (2013, 2013)
Alloying of the surface layer of aluminum with titanium (Ti + Cu) has been carried out. The studies of the elemental and phase composition, the state of the defect substructure of the surface layer modified with an electron beam have been realized. It is shown that the liquid phase alloying of aluminum allows one to form a multiphase submicrocrystalline structure with high strength and tribological properties in the surface laye